Application of cross-cultural communication theories in Malaysian Chinese literature in English a systematic review - Tian, Maodong; Ikmal, Mohd Shahremy (Edelweiss Applied Science and Technology, 2026)
This systematic review aims to examine how cross-cultural communication theories have been applied in the study of Malaysian Chinese literature written in English, with a focus on identifying dominant theoretical approaches, thematic concerns, and gaps in current scholarship. Using the PRISMA 2020 framework, the study systematically searched Web of Science and Scopus and initially retrieved 199 records. After duplicate removal and screening based on predefined inclusion and exclusion criteria, 17 peer-reviewed journal articles were selected for qualitative thematic synthesis. The review shows that theories such as hybridity, diaspora, cultural identity, translation, and postcolonial critique have been widely used to interpret Malaysian Chinese literary texts in English. However, theoretical application remains uneven, with most studies focusing on canonical authors and relying on limited methodological approaches. Interdisciplinary integration is still insufficient, and emerging literary voices remain underexplored. The study concludes that Malaysian Chinese literature in English provides a valuable site for examining identity negotiation, intercultural dialogue, and decolonial critique in postcolonial and multicultural contexts. It also suggests the need for broader theoretical integration, greater methodological diversity, and more inclusive literary representation in future research.